REPRESENTASI KEBUDAYAAN INDONESIA DALAM MUSIK VIDEO WONDERLAND INDONESIA KARYA ALFFY REV (Analisis Semiotika Charles Sander Pierce) (E-Jurnal Medium, 2022)
The culture and characteristics of a region or country are forgotten due to the influence of globalization, one of which is in Indonesia. The popularity of a culture is very dependent on how the mass media expose the cultures that are popular in a country. One of the media that is often used to campaign for its culture is through music videos on the YouTube social media platform. Wonderland Indonesia's music video has cultural elements that are components of research and are examined through the signs in the music video which includes audio and visual elements. The research method used is descriptive qualitative using the semiotic theory of Charles Sander Pierce to analyze and interpret the data in the form of signs in the music video. In the research phase, the authors classify and identify each scene in the music video, then interpret it using Charles Sander Pierce's Triangle of Meaning Theory, namely Sign, Object, Interpretant (interpretation) with a focus on icons, indexes, symbols. From the results of this study, it was concluded that Wonderland Indonesia's music video represents the culture of the provinces of Kalimantan, Sulawesi, Papua, East Nusa Tenggara, Bali, West Java, Central Java, Sumatra, Riau. Wonderland Indonesia's music video tries to invite the audience and the Indonesian people to get to know and appreciate the culture of each region. Keywords: Representation of Indonesian Culture, Music Video Wonderland Indonesia, Semiotics Analysis.